Studi Kajian Bisnis Tambang Uang Digital (Cryptomining) Dalam Konteks Ijarah - Mochammad Ichsan Maulana; Asep Dede Kurnia; Ayi Nurbaeti (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
Industrial revolution 4.0 bring up a new digital currency called cryptocurrency. This also brings a miners who works as an intermediaries to validate each transaction. This research aims to; Explain the Cryptomining, as well as an analysis of points in the Ijarah contract that are relevant to the activities. As for the step by step to mine the coins are as follows; assembling mining rigs, filtering coins, setting up applications, selecting the pools, then proceeding to mine along with routine maintenance, until finally receiving a reward. The study was conducted using a qualitative methods. Researcher collects data by acting as one of the cryptominer. Researcher took most references in the MUI fatwas to conduct analysis, as well as developing of hypotheses in the equalization of the Ijarah covenant towards the process in the Cryptomining activities. The results of this study show that the activities of Cryptomining, are mostly in accordance with the terms of the Ijarah contract. The Miners are equated with Mu'jir, cryptocurrency users as musta'jir, transactions that are processed as benefits, and prizes as ujrah. The mining activity itself is a muamalah activity which is mostly carried out digitally through internet media. Even so, there is still confusion in the terms of payment of the ujrah. Among other things like 'cash as the required payment'. The provisions provided at MUI DSN NO: 28 / DSN-MUI / III / 2002 about money trades, (which in this case relates to the media of the ujrah payment). More on this matter requires ijtihad from clerics, especially DSN MUI.